2020
DOI: 10.1177/1753193419900490
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical and biomechanical assessment of the interosseous membrane of the cadaveric forearm

Abstract: Ten cadaveric specimens underwent biomechanical assessment on a motorized jig with an in-built torque sensor. A differential variable reluctance transducer was placed on the central bundle of the interosseous membrane to detect changes in strain. Torque was measured with an intact interosseous membrane and a sectioned central bundle of the interosseous membrane. Changes in strain and torque were plotted against the degree of rotation of the cadaveric forearms. We found that the overall magnitude of strain to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Based on 10 specimens, Bin Abd Razak et al. (2020) described that IOMs consisted of five entities: the CB, accessory bundle, distal oblique bundle, proximal oblique cords and dorsal oblique accessory cords.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on 10 specimens, Bin Abd Razak et al. (2020) described that IOMs consisted of five entities: the CB, accessory bundle, distal oblique bundle, proximal oblique cords and dorsal oblique accessory cords.…”
Section: Discussionmentioning
confidence: 99%
“…The interosseous membrane (IOM) is a forearm stabilizer and has been traditionally described as one major central band (CB) with two oblique bands, one proximal and one distal (Masouros et al., 2019; Skahen et al., 1997). Other studies have described five structures for the IOM: the proximal oblique cord, dorsal oblique accessory cord, CB, accessory band and distal oblique band (Bin Abd Razak et al., 2020; Noda et al., 2009). Reconstruction of the IOM may be necessary following injury, for example, to correct instability encountered with an Essex–Lopresti instability (Skahen et al., 1997; Tejwani et al., 2005; Tomaino et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Forearm rotation follows the axis directed from the radial head to the ulnar fovea, occurring with full range of motion and physiological stability when forearm bones and soft tissues stabilizers of PRUJ, MRUJ, and DRUJ are preserved [22]. Recent findings have suggested that PRUJ and MRUJ are probably more critical than IOM for forearm rotation, while IOM provides static longitudinal stabilization of the forearm and less so as a rotational stabilizer [23].…”
Section: Discussionmentioning
confidence: 99%
“…Two-locker injuries 1.2I PRUJ dislocation-IOM rupture Rethnam [23], Sharma [24], Obert [25], El Ibrahimi [28], Watanabe [27], Koulali-Idrissi [29] 1.2 IU PRUJ dislocation-IOM rupture-ulna fracture Rehim [5] 1.2IR PRUJ dislocation-IOM rupture-radius fracture Rao [38], Haddad [39], Linzel [40], Mehara [41], Cherif [42], Simpson [45], Shamian [43], Singh [44] 1.2RIU PRUJ dislocation-IOM rupture-ulna fracture-radius fracture Ouakrim [63] 2I.3 IOM rupture-DRUJ dislocation Wassink [30], Szabo [31], Bruckner [32], Carlsen [33] 2IR 1.3 PRUJ dislocation-DRUJ dislocation Leung [9], Verettas [10], Potter [11], Nishi [12], Spicer [13], Papageorgiu [14], Wong [35], Tosun [36], Raghavendra [37] Three-locker injuries [19,41], closed reduction and percutaneous DRUJ pinning [15,18], and open reduction with radial head fixation or ligamentous repair [14,16,17]. In two-locker injuries with ulna and/or radius shaft fracture, forearm bones must undergo osteosynthesis.…”
Section: Type Lesion Description Authorsmentioning
confidence: 99%
“…The accessory bands are distinct structures that are more distal and less substantial than the CB. They vary in number and are differentiated from the CB by thickness more than visual appearance 2-4 (Fig. 1-B).…”
Section: Anatomymentioning
confidence: 99%